The Quality and Distribution of Andesite Rock for Construction Materials in Kokap and Temon District, Kulon Progo Regency, Yogyakarta–Indonesia - Tego Lenggono; Doni Prakasa Eka Putra; Agung Setianto (Geological Engineering Department Universitas Gadjah Mada, 2019)
The construction projects that are currently being carried out in Kulon Progo Regency, Yogyakarta Special Province, Indonesia, started on 2018, are large-scale projects. The projects include the construction of airports, seaports, industrial estates, southern crossing lanes and the construction of Menoreh lanes. The large-scale projects require a very large supply of andesite rocks for material construction. In Kulon Progo Regency itself, there is a huge potential of andesite rock relate to two geological formations (Kebo Butak and Andesite Intrusion) exist in the region, which is found mostly in Kokap District and partly in Temon District. One parameter that determines the quality of andesite rock is their compressive strength. Due to weathering, not all of the andesite in both formation can be classified as good quality rocks. According to Indonesian Standard, theminimum compressive strength of natural stone for stakes and curbstone is 500 kg/cm2 , for lightweight building foundation is 800 kg/cm2 , for medium building foundations is 1000 kg/cm 2and for heavy building foundations is 1500 kg/cm 2 . Based on this background, this paper have objectives to know the quality of andesite rock exist in the research area and to determine the zonation of good quality andesite rock for building and road materials in the research area. Field observation were conducted to map the occurrence of andesite rock. Totally 68 rock samples were collected during field observation and tested by point load test method to know its compressive strength value. The distribution of good quality rock in the research area were determine based on spatial analysis procedure in geographical information system. Results show that andesite rocks found in research area have a compressive strength ranging from 167.12 kg/cm 2 to 2783.37 kg/cm 2 . From 53 samples taken from igneous rock intrusion, it showed that 7.55 % had low quality, 13.21 % had medium quality, 30.19 % had good quality and 49.06 % had very good quality. From the 16 samples taken from the Kebobutak Formation, it showed that 12.50 % had low quality, 18.75 % had good quality and 67.75 % had very good quality. The final map of rock quality zonation reveals 28.92 % of research area classify as low quality, 2.52 % medium quality, 37.68 % good quality and 30.88 % very good quality. It can be concluded that almost 70 % of andesite in the Kokap and Temon District can be used for the running large scale projects.